Gestão pública municipal de Ingaí-MG: uma avaliação interpretativa - Costa, Fabiana Kenia Silva (2019)
Public management indicators are tools created to aid in the strategic decision-making process, contributing to a more efficient and effective management performance. In view of this consideration, the present research aimed to analyze in a specific way the resul ts of the Municipal Public Management Index (IGPM) of the municipality of Ingaí, as well as the interpretation made by members of its political class and public policy management councils (2017-2020) and the last two municipal administrations (2009-2012 and 2013-2016). The index is divided into four dimensions of public administration, namely: socio-political, institutional-administrative, economic-financial and socio-environmental dimensions. These categories of analysis allow delimiting the predominant public management models in a municipality. The results of the sociopolitical dimension indicated the existence of four public consortia and eight public policy management councils. Regarding the institutionaladministrative dimension, Ingaí does not have any indirect administration entity and among the legal instruments of planning it only have the code of works, the law of urban perimeter and the law of tipping. In the economic-financial dimension, tax on urban property and territorial property (IPTU), service tax of any kind (ISSQN) and some fees are used as collection instruments. Regarding the socio-environmental dimension, Ingaí does not have any legislation that deals with the environment, the urban cleaning service is done by the city's own servers, does not is performed selective waste collection and the water of the municipality is treated while the sewage is thrown directly into a stream. The study identified that there is not a predominance of any of the dimensions of analysis, indicating that t he municipality partially appropriates traits of the different models of public administration.